Metabolic dysfunction-associated steatotic liver disease (MASLD) can be a possible predictive factor of incident CKD: NAGALA cohort study - Yuriko Ono; Kimiko Sakai; Takuro Okamura; Hiroshi Okada; Akihiro Obora; Takao Kojima; Masahide Hamaguchi; Michiaki Fukui (PLoS ONE, 2025)
Background A decade-long follow-up study identified metabolic dysfunction-associated fatty liver disease (MAFLD) as an independent predictor for the onset of chronic kidney disease (CKD). In 2023, a Delphi consensus introduced the term metabolic dysfunction-associated steatotic liver disease (MASLD) as an updated nomenclature. This study aims to evaluate whether MASLD, as the newly defined concept of steatotic liver disease, functions as an independent risk factor for CKD development. Additionally, the study seeks to examine the association between MASLD and CKD, while identifying contributing risk factors. Methods This research involved a retrospective cohort study conducted on individuals participating in health checkups at Asahi University Hospital, Japan, from 1994 to 2023. Logistic regression analysis was employed to investigate the relationship between MASLD and the incidence of CKD over a five-year follow-up period. Results A total of 15,873 participants were included in this study. The incidence of CKD was highest among individuals with MASLD (9.5%). Multivariate analysis demonstrated that MASLD was significantly associated with an increased risk of CKD, with an odds ratio (OR) of 1.37 (95% CI 1.12–1.67, p = 0.002). Additional factors such as age (OR 1.04, 95% CI 1.03–1.05, p < 0.001) and estimated glomerular filtration rate (eGFR) (OR 0.88, 95% CI 0.87–0.89, p < 0.001) were also identified as significant predictors of CKD. These findings suggest a robust association between MASLD and an elevated risk of CKD compared to individuals without steatotic liver disease or cardiometabolic risk factors. Conclusions This study establishes MASLD as a significant risk factor for CKD onset. Effective identification and management of MASLD cases are essential to mitigate the incidence of CKD.